Degree-Based Topological Descriptors of Hexaphenylbenzene Molecule Graphs - Alsharafi, Mohammed; Akar, Mutlu; Zeren, Yusuf; Alameri, Abdu (TAYLOR & FRANCIS LTD, 2024)
Degree-based topological descriptors of chemical structures may help to measure the physico-chemical and nano-properties, which are necessary for the growing industry. Hexaphenylbenzene is a chemical structure that plays a significant role in a wide variety of applications in organic electronic materials and liquid crystals, crystal engineering, and other polymeric materials, which are among the most active research areas of investigation in chemistry, biology, and drugs. In this study, in view of the mathematical formulation and analysis of structures, some topological descriptors of the chain molecular graph of hexaphenylbenzene L-n are studied. Moreover, using MATLAB the results are analyzed and the relationship between topological indices and polynomials in the chain of hexaphenylbenzene L-n, which portrays the physio-substance properties has been deduced. These numerical values correlate structural facts, chemical and biological activities, and physical characteristics. The results obtained could help us learn more about the properties of the chain of hexaphenylbenzene.
Keywords: Topological descriptors; molecular graph; hexaphenylbenzene chain; ZAGREB INDEXES; IRREGULARITY; CONNECTIVITY; Chemistry